2021
DOI: 10.21873/invivo.12519
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Composition Changes in T-cell Subpopulations After Chemotherapy in Patients With Gastric Cancer

Abstract: Background/Aim: New therapeutic agents and prognostic biomarkers for gastric cancer are needed. We analyzed the composition of peripheral blood T-cell subpopulations in response to chemotherapy in patients with gastric cancer. Patients and Methods: Peripheral blood samples were collected from patients diagnosed with gastric cancer before and after chemotherapy (FOLFOX; oxaliplatin, and leucovorin). Peripheral blood mononuclear cells were isolated. Patients were divided into responder (n=5) and non-responder g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Investigations into alterations in the numbers and proportions of PBMC cells between tumor patients and healthy individuals have already started 34 - 36 . Studies have shown that the presence of CD8+ tumor-infiltrating lymphocytes is associated with favorable patient prognosis while the presence of immunosuppressive regulatory T cells (Tregs) and macrophages is adversely correlated with survival outcomes 37 . Circulating NK cells and monocytes in the peripheral blood can also be used as indicators of the likelihood of progression-free survival and overall survival 32 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into alterations in the numbers and proportions of PBMC cells between tumor patients and healthy individuals have already started 34 - 36 . Studies have shown that the presence of CD8+ tumor-infiltrating lymphocytes is associated with favorable patient prognosis while the presence of immunosuppressive regulatory T cells (Tregs) and macrophages is adversely correlated with survival outcomes 37 . Circulating NK cells and monocytes in the peripheral blood can also be used as indicators of the likelihood of progression-free survival and overall survival 32 , 38 .…”
Section: Discussionmentioning
confidence: 99%